Pola Relasi Suami Istri pada Pernikahan Siri di Kalangan Santri: Perspektif Konstruksi Sosial Studi Kasus di Dusun Blok Pesantren Desa Sumber Kalong Kecamatan Wonosari Kabupaten Bondowoso - Ahmad Muktafi (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study examines the pattern of husband-wife relations in unregistered (siri) marriages among santri in Blok Pesantren Hamlet, Sumber Kalong Village, Bondowoso Regency, using the theory of social construction. The phenomenon is notable due to three unique conditions imposed by religious leaders: a ban on sexual relations, no obligation for financial support, and mandatory family supervision during dates. This field research employed a qualitative approach through in-depth interviews with siri marriage participants, religious figures, and families. Findings reveal that such marital arrangements emerge as a response to economic limitations, concerns about promiscuity, and the strong authority of religious teachers. Through the lens of social construction theory—externalization, objectivation, and internalization—the practice is perceived and legitimized by the participants as religiously valid, despite neglecting certain spousal rights and duties under state law. The study highlights a negotiated reality between religious values, socio-economic conditions, and community norms.